2021
DOI: 10.3390/ijms22147451
|View full text |Cite
|
Sign up to set email alerts
|

Liver Bile Acid Changes in Mouse Models of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease characterized by progressive cognitive impairment. It is hypothesized to develop due to the dysfunction of two major proteins, amyloid-β (Aβ) and microtubule-associated protein, tau. Evidence supports the involvement of cholesterol changes in both the generation and deposition of Aβ. This study was performed to better understand the role of liver cholesterol and bile acid metabolism in the pathophysiology of AD. We used male and female wild-type control (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…To elucidatethe role of BAs in the liver-brain axis in MUDs, this study profiled plasma BAs,finding that the concentrations of several key BAs were significantly lower in MUDpatients than in HCs. These BA deficiencies during METH withdrawal were consistentwith psychiatric comorbidities observed in MUDs, providing further evidence that BAshave neuroprotective functions in neurodegenerative diseases ( 40 ). The total BA concentration was found to correlatenegatively with both HAM-A and HAM-D scales, but positively correlated with theconcentrations of the neurotransmitters, choline and GABA, suggesting thatexcessively low total BA was associated with worse psychiatric comorbidities.…”
Section: Discussionsupporting
confidence: 73%
“…To elucidatethe role of BAs in the liver-brain axis in MUDs, this study profiled plasma BAs,finding that the concentrations of several key BAs were significantly lower in MUDpatients than in HCs. These BA deficiencies during METH withdrawal were consistentwith psychiatric comorbidities observed in MUDs, providing further evidence that BAshave neuroprotective functions in neurodegenerative diseases ( 40 ). The total BA concentration was found to correlatenegatively with both HAM-A and HAM-D scales, but positively correlated with theconcentrations of the neurotransmitters, choline and GABA, suggesting thatexcessively low total BA was associated with worse psychiatric comorbidities.…”
Section: Discussionsupporting
confidence: 73%
“…Despite the profound modulatory impact of gut microbiota on bile acids (i.e., deconjugation, dehydrogenation, and dihydroxylation of primary bile acids), bile acid metabolism that occurs in the germ-free mice is rather complex. Previous studies have indicated high variability in bile acid metabolism between germ-free and conventional mouse models 90 ; the phenotypes conceivably depend on diet, sex, genetic background, and the respective composition of the microbiota in the conventional control groups 90 , 91 . The results herein showed lower levels of primary bile acids in the GI tract of GF mice with a few exceptions in tauro-conjugated primary bile acids which had a higher abundance in this mouse group (i.e., tauro-α/β-muricholic acid, taurocholic acid, and an isomer of taurocholic acid).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to chronic hyperglycemia also exacerbates AD neurodegeneration and cognitive impairment in AD animals [ 70 , 71 ]. Notably, a large body of preclinical research and prospective cohort studies indicate that liver metabolic alterations or dysfunction could precede progressive cognitive decline and other typical symptoms of AD [ 20 , 72 , 73 ]. The liver is the first organ to exhibit metabolic dysfunction with AD progression [ 74 ].…”
Section: Background Of Alzheimer’s Diseasementioning
confidence: 99%
“…Elevated serum cholesterol levels have been shown to positively associate with an increased risk of dementia, while certain cholesterol-lowering therapies can reduce the production of Aβ [ 91 , 92 ]. Results from another study, which measured hepatic cholesterol and its metabolites in animals, revealed a fundamental defect of liver cholesterol in APP/PS1 and App NL-G-F mice; in particular, impaired bile acid synthesis was observed [ 72 ]. Since bile acid synthesis plays a pivotal role in the excretion of cholesterol, these results collectively suggest that the overall hepatic metabolic profile is compromised in the progression of AD.…”
Section: Liver Dysfunction and Ad Pathologymentioning
confidence: 99%